Nonprofit Organizations in the Knowledge Based Economy – Organizational Development and Professionalization - Katalin Dobrai; Ferenc Farkas (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Kotor, Montengero, 10-11 September 2015, 2015)
International research results underpin that turbulent, continuously changing environment makes everyday operations for nonprofit (nongovernmental, voluntary) sector organizations harder. It also can be observed that in this situation, nonprofit organizations acquire knowledge from business sector organizations which enables them to improve their structures and processes. They implement methods of the business sector as means of ensuring long term existence, better performance and sustainable success. In recent years, this process has generated new dilemmas for those who are concerned with the future of this sector: if and how the strengthening focus on knowledge processes such as learning and development of individuals working for nonprofit organizations impact organizational knowledge and organizational development and, how important professionalization is for them. The goal of this paper is, to give an overview of special issues of learning and growing professionalization of non profit organizations, and to contribute to the research of these processes. Empirical evidence is provided on the base of a large sample survey that involves approximately 1.000 Hungarian foundations or associations. With the help of the research findings the paper shall expand our general knowledge about professionalization trends in the sector, and also provide deeper insight in details of the relationship between participation in organizational development programs and becoming more professional in everyday operations and services.
Keywords: L30; O15; 330; nonprofit organizations; learning; professionalization; knowledge; development